Juegos tradicionales como mecanismo de generación de identidad cultural en estudiantes de educación básica de la Unidad Educativa Milenio Salinas, parroquia Salinas, cantón Guaranda, año 2023 - Parco Parco, Franklin Ismael (2024)
The current research explores the impact of ancestral recreational activities on the cultural identity of the students of the Milenio Salinas primary education institution belonging to the parish that bears the same name, within an area marked by globalization and the prevalence of digital platforms. It focuses on the system of action as vehicles of communication in the cultural framework, essential for the transmission and preservation of values and customs in an era characterized by cultural homogenization. Methodologically, the research adopts a mixed approach, combining qualitative and quantitative methods. Surveys, interviews and participatory observation were used to collect accurate and detailed data on the practice and perception of traditional games in the educational environment. This approach allows a more complete understanding of the cultural and communicative dynamics in the educational unit. The results indicate that traditional games have a significant role in strengthening identity in terms of self-identification in students. Because these games, among which "blind man's chicken, hopscotch, bagging, marbles, spinning tops" stand out, not only facilitate intergenerational communication, but also promote a sense of belonging and social cohesion. The practice of games of typical origin in curricular and extracurricular settings encourages meaningful interaction and the dissemination of traditions, contributing to the sociocultural development of students by revaluing traditions.